MODEL KOMUNIKASI DALAM PEMBENTUKAN NILAI DAN PERILAKU KELOMPOK PENOLAK VAKSIN COVID-19 DI MEDIA SOSIAL (STUDI NETNOGRAFI PADA KOMUNITAS PENOLAK VAKSIN DI FACEBOOK) - Fathia Islamiyatul Syahida, - (2022)
The topic of vaccination and the anti-vaccine movement become a public focus during the Covid-19 pandemic. Currently, the anti-vaccine movement has used social media, especially Facebook, to convey its rejection, until special communities have emerged to reject vaccines. This shows that computer-mediated communication has brought new changes in the process of delivering messages and managing relationships between individuals. The purpose of this study was to find out how the communication model in the formation of values and behavior of the Covid-19 vaccine refusal group in the Facebook online community. To achieve the research objectives, the researcher used a qualitative approach with the netnographic method. Field data were taken from observations of participating in one of the vaccine refusal communities on Facebook and interviews with vaccine refusal actors in that community. The informant selection technique uses a purposive sampling technique that focuses on key informants selected based on the results of observations. The results of the study indicate that the construction of values built regarding vaccines in the community is related to religious, political, and health values. An interesting finding from the value aspect is the contemporary narrative regarding vaccines being haram and violating the provisions of Allah SWT, and is supported by the trend of vaccine conspiracy related to the political sector. The reality of the Covid-19 vaccine refusal in the online community shows the new dynamics of the risks faced, such as the threat from the Facebook institution and the compromise strategy undertaken by the vaccine refusal group to maintain its existence. There are two communication models found, namely the communication model between vaccine refusal and communication model between vaccine refusal and pro-vaccine. The model shows the lower the perception gap between individuals, the higher chances of forming group values and behavior constructs.